PURCHASE BEHAVIOR : ONLINE TOUR PACKAGE - Hamdan, Hamdan; Yuliantini, Tine (Dinasti Publisher, 2021)
The purpose of this study was to analyze a model of online tour package purchasing behavior which is influenced by the perceptual aspects of review ratings, perceived risk, trust and purchase intention. The research design used a combination of exploratory, descriptive-quantitative research. The population and sample selection uses consumers in West Jakarta who will purchase tour packages online. Determining the number of samples using purposive sampling technique and will be distributed to 203 consumers. These findings prove that the rating review positive effect on trust and perceptions of risk. Perceptions of risk have a negative effect on trust and purchase intention. Trust has a positive effect on purchase intention. This is an important consideration for business actors in making future marketing strategy decisions to achieve competitive advantage.